The Role of Enzymes. - Anna Brady (Video Education Australiasia, 2009)
"Enzymes are the critical ingredient in every organism that make life possible. They are catalysts and drive every chemical reaction that takes place in the human body, enabling our bodies to be built from proteins, carbohydrates and fats." -- Back cover.